Modified graphite electrode material and preparation method and application thereof
By coating the surface of graphite particles with a fluorosilicone acrylate copolymer to form a stable SEI layer, the problem of unstable interface between graphite anode and electrolyte in lithium-ion batteries is solved, improving battery capacity and cycle performance, achieving efficient interface transport and stability, and making it suitable for large-scale industrial applications.
Patent Information
- Application Number
- CN202410808101.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-21
- Publication Date
- 2025-12-23
AI Technical Summary
Existing binders cannot effectively solve the problem of unstable interface between graphite anode and electrolyte in lithium-ion batteries, leading to a decline in electrochemical performance and cycle stability, which limits the capacity, capacity retention and rate performance of lithium-ion batteries.
Modified polymers, especially fluorosilicone acrylate copolymers, are used to coat the surface of graphite particles to form a stable SEI layer, which prevents graphite from directly contacting the electrolyte, promotes lithium-ion transport at the interface, and improves battery performance.
By forming a stable fluorine-containing SEI layer, the capacity and its retention rate of lithium-ion batteries are significantly improved, the cycle performance and rate performance of the batteries are enhanced, and the occurrence of side reactions is reduced. The process is low-cost and simple, making it suitable for large-scale industrial applications.
Smart Images

Figure CN121192126A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of battery electrode, further relates to a modified graphite electrode material and a preparation method and application thereof. BACKGROUND
[0002] With the rapid growth of global electric vehicle market and the increasing demand of user experience of portable electronic products, the demand for power supply equipment is increasing, and the new generation of energy storage equipment represented by lithium ion battery is also increasingly valued, and the development of high-performance lithium ion battery has become an inevitable trend.
[0003] Graphite has become the most commonly used negative electrode material in lithium ion batteries due to its low cost, low lithium potential and high electrical conductivity. The current industrial graphite electrode is generally prepared by coating a water dispersion of graphite, dispersant, conductive agent and binder on a copper current collector and then rolling. The binder, as an important component of the graphite electrode, directly affects the electrochemical performance of the lithium ion battery.
[0004] There are many types of binders for industrial graphite negative electrodes, mainly including polyvinylidene fluoride, polymethyl methacrylate, butadiene styrene rubber and the like. In order to further match high-performance lithium ion batteries, two or more binders are usually selected for compounding to obtain a composite binder with better comprehensive performance. The current poly methyl methacrylate and butadiene styrene rubber analog binders have been widely used in industry, which not only improves the cycle stability of the battery but also effectively improves the mechanical stability of the graphite negative electrode (active material shedding and pulverization). However, in the liquid electrolyte system, solvent molecules enter the interlayer of graphite, which can cause the peeling of graphite layers and lead to the decrease of the electrochemical performance and cycle stability of lithium ion batteries. The existing binders do not have the ability to solve the instability problem of the electrolyte / graphite electrode interface, thus limiting the full play of the performance of the graphite negative electrode, resulting in the lack of performance of the graphite negative electrode in terms of capacity, capacity retention rate and rate performance in lithium ion batteries.
[0005] From the existing research, the formation of stable SEI (solid electrolyte phase interface) at the electrode / electrolyte interface can significantly improve the capacity and its retention rate of lithium ion battery, improve the cycle performance and rate performance of the battery, and has important practical significance for the further application of high-performance lithium ion battery. Therefore, researchers have proposed various surface modification methods to optimize the performance of graphite negative electrode, mainly including surface fluorination, surface oxidation, coating metal, carbon modification and polymer modification, etc. These modification methods have achieved certain effect, but most of them show the disadvantages of high cost and complicated preparation process, which causes economic and energy loss to some extent. For example, surface fluorination is mostly treated with electrolyte additives or some fluorine-containing small inorganic or organic molecules to make the surface of the particles contain fluorine elements. This treatment method has high cost and cannot be applied on a large scale, and cannot form a firm interface combination and cannot exist stably on the particle surface. For another example, the polymer modification generally uses polytetrafluoroethylene and polyvinylidene fluoride modified particles, which usually need high temperature calcination, and the modification process is complex and the modification effect is limited.
[0006] Therefore, it is of important practical significance for the academic and industrial circles to seek a simple and efficient, low-cost, and compatible graphite modification scheme for the existing graphite negative electrode production line, so that the modified graphite has more excellent comprehensive performance, which can further meet the development requirements of high-performance lithium ion battery and is easy to be applied on a large scale in industry. SUMMARY
[0007] To solve the above problems, the application provides a modified graphite electrode material and a preparation method thereof. The graphite is modified by using a modified polymer. When the modified graphite is used as a battery electrode, it can prevent the direct contact between the graphite and the electrolyte, avoid unnecessary side reactions, and form a stable fluorine-containing SEI layer on the surface of the electrode, promote the interface transmission of lithium ions at the electrode, and improve the performance of the battery.
[0008] Firstly, one of the purposes of the application is to provide a modified graphite electrode material.
[0009] Specifically, the modified graphite electrode material comprises a modified polymer coated on the surface of graphite particles. The modified polymer forms a stable SEI (solid electrolyte phase interface) at the electrode / electrolyte interface, which can significantly improve the capacity and its retention rate of lithium ion battery, improve the cycle performance and rate performance of the battery, wherein the modified polymer is selected from fluorosilicone acrylate copolymer.
[0010] Preferably, in the modified graphite electrode material, the mass of the modified polymer is 1-20% of the mass of the graphite; preferably 5-15%.
[0011] It is worth mentioning that the fluorosilicone acrylate copolymer with fluorinated side groups in the present application forms a coating layer on the surface of the graphite electrode, which can avoid direct contact of graphite particles with electrolyte solvent, inhibit the generation of side reactions of the solvent at the active material interface, and at the same time, can form a stable SEI layer containing fluorine, improve the interface stability, and is beneficial to the efficient transmission of lithium ions at the interface.
[0012] Secondly, the second object of the present application is to provide a preparation method of the modified graphite electrode material of the first object of the present application.
[0013] Specifically, the method comprises the following steps:
[0014] Step one, polymerize the monomer under the initiation of the initiator to obtain a modified polymer;
[0015] Step two, mix the graphite and the modified polymer, and obtain the modified graphite electrode material under the action of the catalyst.
[0016] More specifically, the method comprises the following steps:
[0017] Step one, add the monomer to solvent A, and initiate free radical polymerization by adding an initiator, and after the reaction is completed, the modified polymer is obtained after washing and precipitation; wherein the solvent A is selected from one of toluene and tetrahydrofuran; the washing and precipitation reagent is selected from any one of the combination of toluene, tetrahydrofuran, and methanol, cyclohexane, n-hexane, and n-pentane;
[0018] Step two, add the graphite particles and the modified polymer to solvent B, and add the catalyst to make the alkoxysilane perform hydrolysis reaction, and obtain the modified graphite slurry under high temperature, remove the solvent in the vacuum drying box, and finally grind to obtain the modified graphite electrode material; the solvent B is selected from one of tetrahydrofuran and toluene.
[0019] Further, the monomer includes components of fluorinated propenoate, methyl propenoate, and alkoxysilane; wherein the molar ratio of the amount of use of the fluorinated propenoate, the methyl propenoate, and the alkoxysilane is 1-20:80-99:1-10; preferably 5-15:85-95:5-8.
[0020] Further, the fluorinated propenoate is selected from one or a combination of dodecafluoroheptyl methacrylate, nonafluorohexyl methacrylate, octafluoropentyl methacrylate, hexafluorobutyl methacrylate, pentafluoropropyl methacrylate, and trifluoroethyl methacrylate.
[0021] Further, the methyl propenoate is selected from one or a combination of pentyl methacrylate, butyl methacrylate, propyl methacrylate, ethyl methacrylate, and methyl methacrylate.
[0022] Further, the alkoxysilane is selected from gamma-methacryloxypropyltrimethoxysilane. The alkoxysilane can provide affinity sites with the graphite particles, and the fluorosilicone acrylate copolymer can be stably coated on the surface of the graphite electrode.
[0023] It is worth mentioning that the present application uses a polymer material similar to the chemical structure of the industrial mature lithium ion battery graphite electrode adhesive (polyacrylate and butadiene rubber analogue) to modify the graphite electrode, so there is no need to worry about the interface problem of the modified graphite and the adhesive, and the presence of silane coupling agent on the polymer backbone also makes the polymer and graphite form a good interface.
[0024] Further, the initiator is selected from one or a combination of azobisisobutyronitrile, azobisisoheptyl nitrile, dibenzoyl peroxide, and dicumyl peroxide; the amount of initiator is 1-2% of the total mass of the polymerized monomers; preferably 1.2-1.5%.
[0025] Further, the catalyst is selected from one or a combination of dibutyltin dilaurate, dibutyltin diacetate, dibutyltin bis(dodecylthio), and stannous octoate; the amount of catalyst is added based on the mass of the entire reaction system, generally 5-20 μL of catalyst is added to a 10 g reaction system, preferably 10-15 μL.
[0026] Further, in step one, the reaction conditions are as follows: the reaction temperature is 60-70℃, the reaction is carried out for 3-6 h, then the temperature is raised to 75-80℃, and the reaction is carried out for 1-3 h.
[0027] Further, in step two, the reaction temperature is 60-80℃, the reaction is carried out for 6-8 h; the temperature of the vacuum drying oven is 60-100℃, the vacuum degree is -0.06 to -0.1 MPa, and the drying time is 12-14 h; the grinding container is an agate mortar, and the grinding time is ≥20 min.
[0028] Thirdly, the present application provides the application of the modified graphite electrode material of any one of the objects of the present application.
[0029] Specifically, the modified graphite material provided by the present application can be used for the negative electrode of a lithium ion battery.
[0030] Further, the preparation method of the negative electrode of the lithium ion battery is as follows: mixing the modified graphite electrode material with a cellulose dispersion solution, adding a binder and water, stirring for 2-4 h, placing on a current collector, using a 25-200 μm thick doctor blade coater to form a film, and drying to obtain the negative electrode of the lithium ion battery.
[0031] Further, the cellulose dispersion liquid concentration is 0.5-1.5% of the aqueous solution, the amount is 0.5-1.5% of the modified graphite electrode material mass; the binder is polyacrylate-styrene butadiene rubber analogue, the concentration is 35-45% of the aqueous suspension, the amount is 0.5-1.5% of the modified graphite electrode material mass; after mixing and stirring, the modified graphite electrode slurry with solid content of 45-52% is obtained.
[0032] It is worth mentioning that the fluorosilicone acrylate copolymer provided by the application includes a methacrylate segment structure, which is similar to the structure of the binder used, can produce good interface combination with the polyacrylate binder, and ensures the high interface compatibility between the modified graphite particles.
[0033] Further, the method for drying the lithium ion battery negative electrode is as follows: the temperature of the vacuum drying box is 60-100 DEG C; the vacuum degree is -0.06 to -0.1 MPa; the drying time is 12-14 h.
[0034] Compared with the prior art, the application has the following beneficial effects:
[0035] 1. The fluorosilicone acrylate copolymer used in the application is similar in structure to the current electrode adhesive material (polyacrylate and styrene butadiene rubber analogue), which is used for graphite surface modification, and does not affect the performance of the binder and the existing preparation process, realizes high interface compatibility, effectively solves the performance defects of low capacity and poor capacity retention rate of the current graphite negative electrode due to unstable interface, greatly improves the reversible capacity and capacity retention rate of the graphite electrode, and has simple preparation process, no harsh conditions, low cost, compatibility with existing production lines, great industrialization potential and wide application prospect.
[0036] 2. The functional acrylate (fluorosilicone) modified graphite particles used in the application can not only impart corresponding functions to the graphite electrode, but also ensure the compatibility of the modified graphite and the binder. Moreover, the fluorinated acrylate can prevent the graphite from directly contacting with the electrolyte, effectively avoid unnecessary side reactions, and cause the reduction of various performances of the lithium ion battery; a stable fluorine-containing SEI layer can be formed on the electrode surface, which promotes the interface transmission of lithium ions at the electrode and improves the performance of the battery; the methacrylate segment structure in the fluorosilicone copolymer is similar to the binder used, can produce good interface combination with the polyacrylate binder, and ensures the high interface compatibility between the modified graphite particles; a small amount of siloxane can enhance the affinity with the surface of the graphite particles, ensure the interface compatibility and stability between the modified layer and the graphite particles.
[0037] 3、The present application copolymerizes the acrylate, fluorinated acrylate and gamma-methacryloxypropyltrimethoxysilane by simple free radical polymerization to obtain fluorosilicon modified polyacrylate, then simply blends the fluorosilicon modified polyacrylate with graphite particles under the action of a catalyst to obtain fluorosilicon modified graphite particles, and finally obtains electrode materials with a corresponding thickness through conventional preparation processes of lithium ion battery graphite electrodes. The polyacrylate can form a good interfacial bond with a commonly used type of adhesive (polyacrylate-styrene butadiene rubber analog) in the current industry, eliminating the risk of reduced interfacial stability of the modified graphite particles. The fluorinated acrylate can participate in the copolymerization of the acrylate, imparting excellent solvent resistance to the acrylate, preventing direct contact between the electrolyte solvent and the surface of the graphite particles, greatly reducing the side reactions between the two, thereby improving the capacity and retention rate of the lithium ion battery and the cycle performance and rate performance of the battery. In addition, the fluorine-containing group also helps to form a more stable inorganic fluorine-containing SEI, promoting the transmission of lithium ions at the interface, thereby forming a more stable phase interface; the gamma-methacryloxypropyltrimethoxysilane can form a stable organic-inorganic phase interface, and its participation in copolymerization can make the polyacrylate form a multifunctional siloxane side group, which can undergo a hydrolysis reaction under the action of a catalyst and combine with the hydroxyl groups on the surface of the graphite particles, so that the fluorosilicon modification layer can stably exist on the surface of the graphite particles, ensuring the stability of the functional layer on the surface of the modified graphite. The raw materials used in the present application are low in cost, and the synthesis and preparation method is simple, compatible with existing production lines, and has the potential for large-scale industrial production. BRIEF DESCRIPTION OF DRAWINGS
[0038] Figure 1 NMR spectrum of the fluorosilicon copolyacrylate prepared in Example 1;
[0039] Figure 2 Fluorospectrum of the fluorosilicon copolyacrylate prepared in Example 1;
[0040] Figure 3 Structure diagram of the modified graphite prepared in Example 1;
[0041] Figure 4 Scanning electron microscope image of the modified graphite prepared in Example 1;
[0042] Figure 5 Charge-discharge cycle diagram of the lithium ion battery prepared in Example 2. DETAILED DESCRIPTION
[0043] The present application will be described in detail below in conjunction with specific drawings and examples. It is necessary to point out here that the following examples are only used to further illustrate the present application and cannot be understood as limiting the protection scope of the present application. Some non-essential improvements and adjustments to the present application made by those skilled in the art based on the content of the present application still fall within the protection scope of the present application.
[0044] In the following examples and comparative examples, all raw materials are not particularly limited in their origin, and can be purchased on the market or prepared according to conventional methods well known to those skilled in the art, wherein the adhesive (polyacrylate-styrene butadiene rubber analogues account for about 40% of the overall adhesive) is from Shenzhen Keyi Zhida Technology Co., Ltd.
[0045] Example 1
[0046] The following is used to illustrate the preparation of modified graphite battery material, and the specific preparation process is as follows:
[0047] Step one, preparation of modified copolymer
[0048] Take 4g of dodecafluoroheptyl methacrylate, 12.8g of butyl methacrylate, and 1.24g of γ-methacryloyloxypropyl trimethoxysilane, and add them to a 100mL three-necked flask equipped with a mechanical stirring paddle, a nitrogen gas conduit, and a reflux condenser. Dissolve the above-mentioned monomers in toluene solvent, and add 1% of azobisisobutyronitrile based on the total weight of the reaction monomers as an initiator to initiate free radical polymerization. After reacting at 70°C for 3h, increase the temperature to 80°C for further curing for 1h to improve monomer conversion. After the reaction is completed, pour the product into methanol, precipitate at low temperature, and then dissolve it in tetrahydrofuran and precipitate again using methanol. Repeat this process three times to wash away unreacted monomers and catalysts. Transfer to a vacuum drying oven at 60°C to remove the solvent and obtain the purified fluorosilicon copolyacrylate.
[0049] Figure 1 The hydrogen spectrum of the fluorosilicon copolyacrylate prepared in this example is shown; Figure 2 The fluorine spectrum of the fluorosilicon copolyacrylate prepared in this example is shown. As can be seen from the figure, the characteristic peaks of the three monomers all appear in the fluorosilicon acrylate copolymer, and the characteristic peak corresponding to the carbon-carbon double bond disappears in the polymer, proving that there is no monomer residue and the polymerization process has a high monomer conversion rate.
[0050] Step two, preparation of modified graphite battery material
[0051] Take 2g of graphite and 0.12g of fluorosilicon copolyacrylate prepared in step one, and add them to a 10mL glass vial. Add 4mL of tetrahydrofuran, stir to dissolve, then add 10μL of dibutyltin dilaurate catalyst, and heat to 60°C. Continue stirring for 6h, then pour out the product to obtain a modified graphite slurry. Place it in a vacuum drying oven at 60°C overnight to remove the solvent, and finally use a maroon mortar to grind it thoroughly to obtain modified graphite particles.
[0052] Figure 3The structure diagram of the modified graphite prepared in the embodiment is shown. As can be seen from the diagram, the siloxane group in the polymer main chain can be hydrolyzed to form a chemical bond with the surface of the graphite, and a firm phase interface is formed. The fluorinated acrylate plays a role of dissolving solvent and forming a stable SEI. The butyl methacrylate has a structure similar to that of the adhesive, and thus does not affect the phase interface generated between the modified graphite and the adhesive, and also ensures the compatibility of the phase interface.
[0053] Figure 4 The electron microscope scanning diagram of the modified graphite prepared in the embodiment is shown. As can be seen from the diagram, the graphite is in a sheet shape, and no obvious adhesion and agglomeration occurs between the sheets after modification.
[0054] The following is used to illustrate the preparation of the graphite negative electrode. The specific preparation process is as follows:
[0055] 1 g of the modified graphite electrode material prepared above is weighed, then 1.2 wt.% of the cellulose dispersion liquid prepared in advance is added and mixed and stirred for 3 h, then 0.033 g of the 40% adhesive water dispersion liquid is added, and the mixture is stirred for 3 h to obtain a modified graphite electrode slurry with a solid content of 49.9%. The slurry is placed on a copper current collector, and a 100 μm doctor blade coater is used for doctor coating and molding. Finally, the sample is placed in a vacuum drying oven at 80°C overnight for drying to remove the solvent, and is ready for use.
[0056] The following is used to illustrate the preparation of the lithium ion button cell. The specific preparation process is as follows:
[0057] The graphite negative electrode prepared above is cut into small round sheets with a diameter of 10 mm by a sheet punching machine. In a glove box with a water and oxygen content of <0.01 ppm, a 300 μm thick lithium metal is used as the counter electrode to assemble a CR2032 type lithium ion button cell. The lithium ion button cell is subjected to charge and discharge cycle tests at a voltage range of 0.01-2.5 V and a current density of 37 mA / g.
[0058] The specific capacity and capacity retention rate of the lithium ion battery prepared in the embodiment after the 20th cycle are shown in Table 1.
[0059] Example 2
[0060] In the embodiment, the preparation method of the lithium ion battery is the same as that provided in Example 1, except that the amount of the fluorosilicone copolyacrylate used in the preparation of the modified graphite is 0.2 g.
[0061] The specific capacity and capacity retention rate of the lithium ion battery prepared in the embodiment after the 20th cycle are shown in Table 1.
[0062] Figure 5The charge-discharge cycle diagram of the lithium ion battery prepared in the embodiment is shown. As can be seen from the diagram, after 100 cycles of charge and discharge, the coulombic efficiency is close to 100%, indicating that no side reaction occurs, and the capacity retention rate is 94.5%. The modified graphite electrode provided in the embodiment exhibits ultra-high cycle stability.
[0063] Example 3
[0064] In the embodiment, the preparation method of the lithium ion battery is the same as that provided in Example 1, except that the amount of fluorosilicon copolyacrylate used in the preparation of the modified graphite is 0.24 g.
[0065] The specific capacity and capacity retention rate of the lithium ion battery prepared in the embodiment after the 20th cycle are shown in Table 1.
[0066] Example 4
[0067] In the embodiment, the preparation method of the lithium ion battery is the same as that provided in Example 1, except that the amount of fluorosilicon copolyacrylate used in the preparation of the modified graphite is 0.3 g.
[0068] The specific capacity and capacity retention rate of the lithium ion battery prepared in the embodiment after the 20th cycle are shown in Table 1.
[0069] Example 5
[0070] In the embodiment, the preparation method of the lithium ion battery is the same as that provided in Example 1, except that the thickness of the doctor blade used in the preparation of the graphite negative electrode is 75 μm.
[0071] The specific capacity and capacity retention rate of the lithium ion battery prepared in the embodiment after the 20th cycle are shown in Table 1.
[0072] Example 6
[0073] In the embodiment, the preparation method of the lithium ion battery is the same as that provided in Example 1, except that the fluorinated acrylate used in the synthesis of fluorosilicon copolyacrylate is trifluoroethyl methacrylate, and the amount used is 1.68 g.
[0074] The specific capacity and capacity retention rate of the lithium ion battery prepared in the embodiment after the 20th cycle are shown in Table 1.
[0075] Comparative Example 1
[0076] In the comparative example, the preparation method of the lithium ion battery is the same as that provided in Example 1, except that the graphite used is not modified. In the comparative example, the solid content of the graphite electrode slurry is 49.9%.
[0077] The specific capacity and capacity retention of the lithium ion battery prepared in the present comparative example after 20 cycles are shown in Table 1.
[0078] Comparative Example 2
[0079] The preparation method of the lithium ion battery in the present comparative example is the same as that provided in Example 1, except that the amount of the modified graphite added is 1.11 g (wherein the mass of the graphite is 1 g and the mass of the modified polymer is 0.11 g) when preparing the graphite negative electrode, and the modified graphite electrode slurry is 52.5%.
[0080] The specific capacity and capacity retention of the lithium ion battery prepared in the present comparative example after 20 cycles are shown in Table 1.
[0081] The lithium ion batteries prepared in Examples 1-5 and Comparative Examples 1-2 are subjected to electrical performance testing, wherein the specific capacity and capacity retention after 20 cycles are shown in Table 1.
[0082] Table 1:
[0083] Sample name Specific capacity / mAh g -1 ]] Coulombic efficiency / % Capacity retention / % Example 1 273.2 99.62 96.5 Example 2 282.6 99.73 97.4 Example 3 283.1 99.71 97.3 Example 4 275.3 99.52 96.9 Example 5 266.9 99.54 96.3 Example 6 272.9 99.61 96.7 Comparative Example 1 253.3 99.35 95.5 Comparative Example 2 223.2 99.41 95.4
[0084] As shown in Table 1, the graphite particles in Examples 1-6 are modified by fluorine-silicon, and after 20 cycles of charge-discharge cycling test at a current density of 37 mA / g in the voltage range of 0.01-2.5 V, the specific capacity and capacity retention are still good. The specific capacity of the batteries provided in Comparative Examples 1-2 decays faster than that of the batteries provided in Examples 1-6, and after 20 cycles of charge-discharge, the specific capacity decays by about 1%.
[0085] Further, as shown in Examples 1-3, with the increase of the content of fluorine-silicon copolyacrylate, the capacity and capacity retention of the lithium ion battery increase and tend to be stable, because when the amount of fluorine-silicon copolyacrylate added is 10% of the graphite, a relatively complete coating is formed on the surface of the graphite, which successfully prevents the direct contact between the electrolyte solvent and the graphite surface, inhibits the side reaction between the electrolyte and the graphite particles, and reduces the unnecessary consumption of active lithium ions, so the capacity of the fluorine-silicon modified graphite electrode is significantly improved compared with the unmodified graphite electrode (Comparative Example 1). In addition, the high coulombic efficiency (>99.5%) of the fluorine-silicon modified graphite electrode also shows that the fluorine-silicon modification greatly inhibits the side reaction inside the battery and improves the reversibility of the battery, because the fluorine-containing groups exist on the surface of the graphite, which on the one hand prevents the side reaction between the solvent and the electrode surface, and on the other hand forms a stable fluorine-containing SEI layer on the electrode surface, promoting the interfacial transmission of lithium ions at the electrode.
[0086] Further, from Example 4, it can be seen that the use of a higher content of fluorosilicon copolymerized acrylate has a tendency to reduce the capacity, because a high content of polymer forms a thicker modified layer on the surface of the graphite particles, which easily causes the graphite to agglomerate, and in the process of grinding, the graphite cannot be fully ground and separated, forming graphite-polymer agglomerates, which are difficult to disperse, thereby reducing the performance of the lithium ion battery.
[0087] Further, from Example 5, it can be seen that the capacity of the thin graphite electrode is slightly lower than that of other electrodes, but is still higher than that of the unmodified graphite electrode (Comparative Example 1), because slight agglomeration of the graphite particles produces defects, and when the electrode is thick, the slight agglomeration of the graphite particles does not significantly affect the performance, but when the graphite electrode is thin, the agglomeration is more obvious, and the impact on the performance is more significant.
[0088] Further, from Comparative Example 2, it can be seen that when the solid content in the battery is further increased, that is, when the solid content of the modified graphite electrode slurry is 52.5%, the performance of the battery is deteriorated, because a large amount of graphite cannot be well dispersed under laboratory conditions, and a large amount of agglomerates increases the internal impedance of the battery, greatly deteriorating the performance of the battery and causing the capacity to decrease.
[0089] From the above, it can be seen that the fluorosilicon modified graphite electrode material provided by the present application has better comprehensive performance than unmodified graphite, and the synthesis and preparation method of the fluorosilicon modified graphite electrode material is simple, compatible with existing production lines, and more suitable for the development direction of future high-performance lithium ion batteries.
[0090] The above describes the preferred embodiments of the present application in detail, but the present application is not limited thereto. Within the technical concept of the present application, various simple modifications can be made to the technical solutions of the present application, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be considered as disclosed by the present application, and all fall within the protection scope of the present application.
Claims
1. A modified graphite electrode material comprising a modified polymer coated on the surface of graphite particles, wherein the modified polymer is selected from fluorosilicone acrylate copolymers.
2. The modified graphite electrode material according to claim 1, characterized in that, In the modified graphite material, the mass of the modified polymer is 1 to 20% of the mass of the graphite; preferably 5 to 15%.
3. The method for preparing the modified graphite electrode material according to any one of claims 1 to 2, characterized in that, The method includes the following steps: Step 1: The monomers are polymerized under the initiation of an initiator to obtain the modified polymer; Step 2: Mix graphite and modified polymer, and obtain modified graphite electrode material under the action of a catalyst.
4. The method according to claim 3, characterized in that, The polymer monomers include components fluoroacrylate, methacrylate and alkoxysilane.
5. The method according to claim 4, characterized in that, The fluoroacrylate is selected from one or a combination of dodecafluoroheptyl methacrylate, nonafluorohexyl methacrylate, octafluoropentyl methacrylate, hexafluorobutyl methacrylate, pentafluoropropyl methacrylate, and trifluoroethyl methacrylate; and / or, The methacrylate is selected from one or a combination of amyl methacrylate, butyl methacrylate, propyl methacrylate, ethyl methacrylate, and methyl methacrylate; and / or, The alkoxysilane is selected from γ-methacryloyloxypropyltrimethoxysilane.
6. The method according to claim 4, characterized in that, The molar ratio of the fluoroacrylate, methacrylate and alkoxysilane is 1-20:80-99:1-10; preferably 5-15:85-95:5-8.
7. The method according to claim 3, characterized in that, The initiator is selected from one or a combination of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, and dicumyl peroxide; and / or, The amount of the initiator is 1-2% of the total mass of the polymerizing monomers; preferably 1.2-1.5%; and / or, The catalyst is selected from one or a combination of dibutyltin disilicate, dibutyltin diacetate, di(dodecyl sulfide)dibutyltin, and stannous octoate.
8. The application of the modified graphite electrode material according to any one of claims 1 to 2, wherein the modified graphite material is used as the negative electrode of a lithium-ion battery.
9. The application of graphite particles according to claim 8, characterized in that, The method for preparing the negative electrode of the potassium-ion battery is as follows: the modified graphite electrode material is mixed with cellulose dispersion, a binder and water are added and stirred, then placed on a current collector, and coated with a scraper with a thickness of 25-200 μm to form a lithium-ion battery negative electrode.
10. The application of graphite particles according to claim 9, characterized in that, The cellulose dispersion is an aqueous solution with a concentration of 0.5-1.5%, and the amount used is 0.5-1.5% of the mass of the modified graphite electrode material; the binder is an aqueous suspension of polyacrylate-styrene-butadiene rubber analog with a concentration of 35%-45%, and the amount used is 0.5-1.5% of the mass of the modified graphite electrode material; after mixing and stirring, a modified graphite electrode slurry with a solid content of 45-52% is obtained.